Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1109/access.2021.3097367
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study on the Effects of Interface Charges and Geometry on Vertical GAA GaN Nanowire MOSFET for Low-Power Application

Abstract: The effects of interface charges on the performances of gate-all-around (GAA) GaN vertical nanowire MOSFETs with different geometries have been studied. Geometrical effect on the gate current of vertical GAA GaN nanowire MOSFET has also been analysed for the first time. In the ideal condition, the circular geometry nanowire (CGN) MOSFET exhibits the best performance with subthreshold swing (SS) of 62 mV/dec, drain-induced barrier lowering (DIBL) of 14 mV/V, and ON/OFF current ratio (I ON /I OFF ) of ∼10 8 . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This allows the acceptor traps to ionize sufficiently and increases the free electron concentration. Previous studies [19]- [21] have shown that triangular nanowires also have an increase in the free electron concentration. The corner effect is primarily responsible for the high performance of device, which is relatively higher than the performance reported in the literature [16], as shown in Table 3.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This allows the acceptor traps to ionize sufficiently and increases the free electron concentration. Previous studies [19]- [21] have shown that triangular nanowires also have an increase in the free electron concentration. The corner effect is primarily responsible for the high performance of device, which is relatively higher than the performance reported in the literature [16], as shown in Table 3.…”
Section: Resultsmentioning
confidence: 85%
“…According to the realization process of gate-allaround poly-SiNW FETs reported in the literature, the sections of these SiNWs have a quasi-circular shape or square shape with rounded edges. Previous work [19]- [21] showed that the shape of SiNW significantly affects the device's performance. Particularly when the SiNW shape is triangular, where the free electron concentration increases near the corners.…”
Section: Introductionmentioning
confidence: 99%
“…Ni silicides have been widely used; moreover, the relaxation of the SiGe layer could be diminished by introducing carbon in the SiGe layers [176][177][178][179]. The SEG process of SiGe suffers from a pattern-dependency problem when, in the profile of the epi-layer, the exposed Si areas in openings (for example, in the S/D regions) in a chip differ for different layouts [19][20][21]38,[180][181][182][183]. The main reason behind this problem is the non-uniform consumption of reactant gases (GeH 4 , SiH 4 , DCS, HCl) over a patterned wafer (global effect) or an array of openings inside a chip (local effect), when the layout of chip is changed.…”
Section: Selective Epitaxy Growth (Seg) Of Sige In S/d Regionsmentioning
confidence: 99%
“…Figure 5 shows the ferroelectric VSAFETs (Fe-VSAFETs) with a self-a metal gate [13]. Fe-VSAFETs have excellent electrical characteristics such as ION/IOF of more than 10 7 , leakage currents of less than 1pA, long retention times, program times of around 100 ns, and the largest memory window (MW) at about 2.3 V. Further studies on GAAFET have been reported, including high-mobility c materials, e.g., Ge/GeSn [14][15][16][17] and III-V [18], and wide bandgap materials, e.g [19,20]. Further studies on GAAFET have been reported, including high-mobility channel materials, e.g., Ge/GeSn [14][15][16][17] and III-V [18], and wide bandgap materials, e.g., GaN [19,20].…”
Section: Introductionmentioning
confidence: 99%